Europe's 1968 : voices of revolt - Gildea, Robert 1952- Hrsg; Mark, James 1972- HerausgeberIn; Warring, Anette 1958- MitwirkendeR (Oxford Univ. Press, 2013)
By the late 1960s, in a Europe divided by the Cold War and challenged by global revolution in Latin America, Asia, and Africa, thousands of young people threw themselves into activism to change both the world and themselves. This new and exciting study of 'Europe's 1968' is based on the rich oral histories of nearly 500 former activists collected by an international team of historians across fourteen countries. Activists' own voices reflect on how they were drawn into activism, how they worked and struggled together, how they combined the political and the personal in their lives, and the pride or regret with which they look back on those momentous years. Themes explored include generational revolt and activists' relationship with their families, the meanings of revolution, transnational encounters and spaces of revolt, faith and radicalism, dropping out, gender and sexuality, and revolutionary violence